Analysis of the atomic structure of CdS magic-size clusters by X-ray absorption spectroscopy. Issue 37 (16th September 2020) - Liu, Ying; Tan, Lei; Cibin, Giannantonio; Gianolio, Diego; Han, Shuo; Yu, Kui; Dove, Martin T.; Sapelkin, Andrei V.
Abstract : A methodology to construct atomistic models of magic-size clusters from X-ray absorption spectroscopy for subsequent simulations and in-depth analysis. Abstract : Magic-size clusters are ultra-small colloidal semiconductor systems that are intensively studied due to their monodisperse nature and sharp UV-vis absorption peak compared with regular quantum dots. However, the small size of such clusters (<2 nm), and the large surface-to-bulk ratio significantly limit characterisation techniques that can be utilised. Here we demonstrate how a combination of EXAFS and XANES analyses can be used to obtain information about sample stoichiometry and cluster symmetry. Investigating two types of clusters that show sharp UV-vis absorption peaks at 311 nm and 322 nm, we found that both samples possess approximately 2 : 1 Cd : S ratio and have similar nearest-neighbour structural arrangements. However, both samples demonstrate a significant departure from the tetrahedral structural arrangement, with an average bond angle determined to be around 106.1° showing a bi-fold bond angle distribution. Our results suggest that both samples are quasi-isomers – their core structures have identical chemical compositions, but different atomic arrangements with distinct bond angle distributions.